A knotted ureteral stent: A case report and review of the literature - Picozzi Stefano; Carmignani Luca (Urology Annals, 2010)
The indications for ureteral stent placement have expanded significantly with the progress of surgical procedures and techniques. Although such stents are now an integral part of contemporary urological practice, their use is not free of complications and consequences. There are very rare descriptions of knot formation in a ureteral stent and the consequences of this occurrence, with only 12 cases previously reported. Here, we report an additional case and review all the literature concerning this urological complication with emphasis on its predisposing factors and conservative and surgical management.